Programming Learning Requirements Based on Multi Perspectives - Layth Khaleel, Firas; Sahari Ashaari, Noraidah; Tengku Wook, Tengku Siti Meriam; Ismail, Amirah (International journal of electrical and computer engineering (Malacca, Malacca), 2017)
Students occasionally find it difficult to learn new programming languages. They often confront unfamiliar programming terms and having difficulty to visualize the processes that happen in computer memory. Weak students find this a burden and end up memorizing the processes without understanding them and their workings. This situation invariably leads students to obtain low grades in their programming subjects. The preliminary investigation of survey was produce in previous work; the results showed that students have experienced ineffective learning, lack of interest towards this course and lack of motivation. Therefore, the main objective of this study is to identify programming learning requirements based on previous work and verified from two perspectives (experts and students). Finally, the result was a group of requirements that should be considered in programming language course